2020
DOI: 10.1155/2020/8379526
|View full text |Cite|
|
Sign up to set email alerts
|

Repurposing Napabucasin as an Antimicrobial Agent against Oral Streptococcal Biofilms

Abstract: Objectives. Disruption of microbial biofilms is an effective way to control dental caries. Drug resistance and side effects of the existing antimicrobials necessitate the development of novel antibacterial agents. The current study was aimed at investigating the antibacterial activities of the repurposed natural compound napabucasin against oral streptococci. Methods. The minimum inhibitory concentration, minimum bactericidal concentration, minimum biofilm inhibition concentration, and minimum biofilm reductio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 61 publications
1
7
0
Order By: Relevance
“…Our data showed that LCG-N25 exhibited significantly lower cytotoxicity on HOKs and HGEs as compared to CHX and NAP. In addition, the antimicrobial activities of LCG-N25 against oral streptococci were significantly enhanced after structural modifications, with almost an eight-fold decrease of MIC against S. mutans as compared to that of NAP (3.91 µg/mL as reported previously) (Kuang et al, 2020), and a 3-fold decrease in MIC as compared to that of CHX. All these data indicate that LCG-N25 is more suitable for the control of oral biofilms as compared to its lead compound NAP.…”
Section: Discussionsupporting
confidence: 64%
See 3 more Smart Citations
“…Our data showed that LCG-N25 exhibited significantly lower cytotoxicity on HOKs and HGEs as compared to CHX and NAP. In addition, the antimicrobial activities of LCG-N25 against oral streptococci were significantly enhanced after structural modifications, with almost an eight-fold decrease of MIC against S. mutans as compared to that of NAP (3.91 µg/mL as reported previously) (Kuang et al, 2020), and a 3-fold decrease in MIC as compared to that of CHX. All these data indicate that LCG-N25 is more suitable for the control of oral biofilms as compared to its lead compound NAP.…”
Section: Discussionsupporting
confidence: 64%
“…* Statistically significant differences compared to the control (P < 0.05); ns, not significant. previously screened a library of bioactive molecules against S. mutans and identified a natural compound NAP showing good antimicrobial activity against oral streptococci (Kuang et al, 2020). However, as an antitumor treatment currently in phase III clinical trials (Sonbol et al, 2019), the mild cytotoxicity of NAP on oral cells may limit its repurposed used in the control of dental caries.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the article titled “Repurposing Napabucasin as an Antimicrobial Agent against Oral Streptococcal Biofilms” [ 1 ], the authors mistakenly generated the line graph of Figure 1(c) using the data from Figure 1(b) . The corrected figure is provided as follows.…”
mentioning
confidence: 99%